ANALISA KOEFISIEN ABSORPSI BUNYI MATERIAL SERAT BATANG KELAPA SAWIT DENGAN GYPSUM MENGGUNAKAN SONIC WAVE ANALYZER - Qory Gunanda; Riad Syech; Muhammad Edisar (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A research has been done in analyzing a coefficient absorption of composite material of oil palm trunk fiber and gypsum using a sonic wave analyzer (SOWAN) and carried out using sound wave of 150 Hz frequency. Sample was formed as a cylinder made from gypsum with 3:5 ratio of water and gypsum, formed a pipe with 7,5 cm outer diameter and heights of 2 cm, 3 cm, 4 cm, 5 cm, and 6 cm (sample thickness). The pipe with the outer diameter of 6 cm was used for making a cavity in the samples and then the composed of oil palm trunk fiber of ± 1 cm length with the variation percentage of fiber of 12,24%, 24,48%, 36,73%, and 48,97% filled in to each sample. Ao (initial amplitude) and A (final amplitude) then were measured by Sonic Wave Analyzer (SOWAN) with the intensity of 65 dB, 70 dB, 75 dB, dan 80 dB. Results of the measurements showed that the bigger percentation of fiber, the higher coefficient of sound absorption andthicker sample produced bigger the coefficient of sound absorption. The biggest absorption coefficient was 0,4957, due to the sample with 6 cm thickness when the intensity was 80 dB and the smallest absorption coefficient was 0,3088, of the sample with 2 cm thickness when the intensity was 65 dB. The maximum absorptioncoefficients of the sample thickness of 2 cm, 3 cm, 4 cm, and 5 cm were 0,3557, 0,3779,0,4155, and 0,4863, respectively. This showed that preparing the sample by method ofarranging the oil palm stem's fiber inside the sample was more effective to absorb the sound for low frequencies (150Hz) if viewed from the standard of absorption coefficientof gypsum was 0.29 for frequency of 150 Hz. Based on the results of this study the absorption coefficients exceed the minimum limit 0.15 as suggested ISO 11654 as a silencer.